2013
DOI: 10.1103/physrevc.88.024903
|View full text |Cite
|
Sign up to set email alerts
|

Testing viscous and anisotropic hydrodynamics in an exactly solvable case

Abstract: We exactly solve the one-dimensional boost-invariant Boltzmann equation in the relaxation time approximation for arbitrary shear viscosity. The results are compared with the predictions of viscous and anisotropic hydrodynamics. Studying different non-equilibrium cases and comparing the exact kinetic-theory results to the second-order viscous hydrodynamics results we find that recent formulations of second-order viscous hydrodynamics agree better with the exact solution than the standard Israel-Stewart approach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
277
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 202 publications
(288 citation statements)
references
References 74 publications
11
277
0
Order By: Relevance
“…VII of Ref. [47] where this result is obtained without moment expansion). All approaches will be compared at the same value ofη, using…”
Section: A Reduced (0+1)-dimensional Vahydro Equationsmentioning
confidence: 81%
See 3 more Smart Citations
“…VII of Ref. [47] where this result is obtained without moment expansion). All approaches will be compared at the same value ofη, using…”
Section: A Reduced (0+1)-dimensional Vahydro Equationsmentioning
confidence: 81%
“…We additionally include the corresponding approximate result obtained by using the second-order viscous hydrodynamic equations of vaHydro is seen to yield the best overall approximation in all situations, with third-order hydrodynamics a close second for sufficiently small specific shear viscosities. We also point out that, among the approximations explored here, the second-order viscous hydrodynamic equations of Denicol et al which were shown in [36,46,47] to work better than Israel-Stewart theory, provide the poorest approximation to the exact solution, in all cases studied.…”
Section: B Pressure Anisotropymentioning
confidence: 99%
See 2 more Smart Citations
“…For (0+1)-d longitudinally boost-invariant expansion of a transversally homogeneous system, the Boltzmann equation can be solved exactly in RTA [9], and the solution can be used to test the various macroscopic hydrodynamic approximation schemes. Setting homogeneous initial conditions in r and space-time rapidity η s and zero transverse flow, π µν reduces to a single non-vanishing componentπ:π µν = diag(0, −π/2, −π/2,π) at z = 0.…”
Section: Testing Vahydro In (0+1)-dimensional Expansionmentioning
confidence: 99%